Fathers, fathering and child psychopathology. (June 2017) - Barker, Beth; Iles, Jane E; Ramchandani, Paul G
Highlights: Father involvement can significantly influence children's developmental outcomes. Increased paternal sensitivity and engagement are associated with reduced child psychopathology. Secure father–child attachment independently predicts decreased adverse child outcomes. Parenting programmes generally do not successfully engage fathers. Paternal engagement in interventions can improve beneficial child outcomes. Abstract : The last few years have seen a steady increase in research addressing the potential influence of fathers on their children's development. There has also been a clearer acknowledgement of the need to study families as a complex system, rather than just focusing on individual aspects of functioning in one or other parent. Increased father involvement and more engaged styles of father–infant interactions are associated with more positive outcomes for children. Studies of paternal depression and other psychopathology have begun to elucidate some of the key mechanisms by which fathers can influence their children's development. These lessons are now being incorporated into thinking about engaging both mothers and fathers in effective interventions to optimise their children's health and development.